AGENDA KEBIJAKAN PUBLIK PADA BADAN PERPUSTAKAAN DAN ARSIP (BPA) KOTA PEKANBARU - hernimawati, hernimawati; dailiati, surya; sudaryanto, sudaryanto (Jurnal Niara, 2017)
In Pekanbaru City Administration there are 43 Regional Devices Work Unit (SKPD), one of the Library and Archive Board (BPA) Pekanbaru City. BPA Has a big agenda in accordance with the vision of "Realization of Information Center and Documentation and Reading Center in Pekanbaru City". Based on pre-survey conducted there are problems that lack of public participation in utilizing the existence of BPA Pekanbaru City and the limited books / references required visitors. This public policy agenda can not be implemented entirely, whereas library and archival development is implemented with the aim of raising awareness, willingness of reading interest for every individual, public, institution and school. In order to realize the highest degree of community education systematically and sustainably as a mandate of the opening of the 1945 Constitution is to educate the life of the nation.The research was conducted at the Library and Archive Board (BPA) Pekanbaru City. Population and sample in this research is State Civil Apparatus that served in Library and Archives of Pekanbaru. The sampling technique used is simple random sampling (simple random). The number of civil servants 36 and daily personnel are 41 persons.From research activities conducted known that the Library and Archives (BPA) Pekanbaru comes as one of the seriousness of the Government of Pekanbaru City in the intellectual life of the nation. BPA Pekanbaru has the task to provide the best service in the field of library and filing. Website managed to be one source and delivery of information BPA Pekanbaru City. Then the BPA is good enough to implement the policies that have been made. From the questionnaires given to the employees, freelance and community personnel (pengaunjung) is known that as many as 17 respondents stated it was good public policy on the Library and Archives (BPA) Pekanbaru. Then as many as 3 respondents stated good enough and 0 for the less good